If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 3) + -5 = 5(x + 4) Reorder the terms: (3 + 4x) + -5 = 5(x + 4) Remove parenthesis around (3 + 4x) 3 + 4x + -5 = 5(x + 4) Reorder the terms: 3 + -5 + 4x = 5(x + 4) Combine like terms: 3 + -5 = -2 -2 + 4x = 5(x + 4) Reorder the terms: -2 + 4x = 5(4 + x) -2 + 4x = (4 * 5 + x * 5) -2 + 4x = (20 + 5x) Solving -2 + 4x = 20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 4x + -5x = 20 + 5x + -5x Combine like terms: 4x + -5x = -1x -2 + -1x = 20 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -1x = 20 + 0 -2 + -1x = 20 Add '2' to each side of the equation. -2 + 2 + -1x = 20 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 20 + 2 -1x = 20 + 2 Combine like terms: 20 + 2 = 22 -1x = 22 Divide each side by '-1'. x = -22 Simplifying x = -22
| x*12+-42+85=246 | | 74=10+4x | | 5y-7+y+27=5y+20-3y | | 7(0)-2(6)=12 | | x^2+y^2+18x+17=0 | | x(x)=16316 | | 190=-8+9x | | 8x-14=-16 | | 7(5x+8)=-x+4 | | 0.10(y-9)+0.12y=0.18y-0.07(10) | | 7(5x+8)=-x+4 | | 8(2x+1)=7x+7 | | 4-9=6+x | | 4-9=6+x | | 4-9=6+x | | x-47=28 | | 4x^3(6)= | | 4=x/2+8 | | 32-4(9-2)=4(T-1) | | -81=-4x+3 | | X+1(4x-2)=2x-1(3x-1) | | 20-3z=7z+8 | | x/10+6=8 | | 2(2x+3)-3=5 | | 4(2x-1)+4=x+25 | | 3.3z-2.3z+0.4=-7.2 | | (4-2i)(6-5i)=0 | | -33=3(4c+5) | | (x+5)2=16x | | x+2(49)=115 | | (5y+2)(3y-1)= | | 3(2x-1)+4=y+25 |